Governance of Nigeria-China economic relations : the case of Kano State Ministry of Commerce and Industry in Kwari Market Kano, Nigeria - Haruna, Haruna Muhammad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Nigeria and China have established diplomatic relations in 1971. The relations between these two countries have blossomed and progressed over the years from political to a more intense economic and trade penetration of the Nigerian markets. However, China seemed to be driven by its crave for economic gain and development in creating conditions necessary for Nigerian trade dependence on China. This was made possible through economic favours to Nigeria, investments, importations and trade domination in the Nigerian markets, manipulation of product quality and price as well as overbearing political influence of China over the Nigerian policy institutions. This study, using dependency and world system theory, examines the governance of Nigeria-China economic relations with reference to the impact of trade in Kwari market Kano State. It also assesses the role of Kano State Ministry of Commerce and Industry and how it influences the Nigerian trade dependence on China using Kwari market as a case in point. The study is based on qualitative method of data collection and its employs semi-structured interviews in gathering information from the respondents. A purposive sampling technique was used to select nine respondents from both the Kano State Ministry of Commerce and Kwari market respectively as its sample size. The data collected for the study were thematically content analyzed. Therefore, the finding shows that the impacts of Chinese trade penetrations onto the Nigerian markets, especially Kwari, influences its trade dependence on China. Similarly, absence of structural policy mechanism by the Kano State Ministry of Commerce and Industry further conditions the Nigerian trade dependence on China in Kwari market. Both internal and external conditions lead to Nigerian trade dependence on China. Finally, the study provides ways of enhancing the weaknesses of policy institutions on the part of Nigeria and trade relations between the two countries in order to achieve mutually beneficial relations